Strategies for Implementing an Arabic Language Environment to Improve Speaking Skills (Maharah Kalam) of Female Students in the Girls’ Dormitory at Rasyidiyah Khalidiyah Islamic Boarding School, Amuntai - Mulyanti , Rhida April; Nuruddaroini, M. Ahim Sulthan; Syihabuddin, Muhammad (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The Arabic language environment (bi’ah lughawiyah) plays an important role in improving the speaking skills (maharah kalam) of female students (santriwati) in Islamic boarding schools, as it functions not only as a medium of communication but also as a means of natural language habituation. In practice, the implementation of a language environment often faces various challenges, such as lack of self-confidence, limited vocabulary, and suboptimal program consistency. These conditions indicate the need for a more in-depth study of strategies for implementing bi’ah lughawiya, especially in female Islamic boarding schools. This study aims to analyze the strategies for implementing an Arabic language environment and its impact on improving the speaking skills of santriwati at Rasyidiyah Khalidiyah Islamic Boarding School in Amuntai. The method used is descriptive qualitative research, with data collection techniques including interviews, observations, and documentation. Data analysis is carried out descriptively-analytically through the stages of data reduction, data presentation, and conclusion drawing, with validity testing through triangulation. The results of the study show that the implementation of bi’ah lughawiyah is carried out through language regulations, vocabulary habituation (mufradat), conversation practice muhadatsah, and intensive mentoring by musyrifah. Formal and non-formal environments support each other in creating continuous language practice. The impact is reflected in increased confidence in speaking, improved vocabulary mastery, and greater fluency in communication among santriwati. Therefore, strengthening program innovation and consistency in implementation is necessary to make Arabic language learning more effective and sustainable.